KESIAPAN GURU MATEMATIKA DI KOTA YOGYAKARTA DALAM MELAKSANAKAN KURIKULUM 2013 - Enika Wulandari; Jailani Jailani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
The purpose of this study is to describe the readiness of  Mathematics teacher in Yogyakarta City to implement the 2013 Curriculum. The readiness aspect consists of insight, attitudes, and infrastructure support. This type of research is a survey research with mixed research (mixed methods). Subjects in the study were 33 Mathematics teachers from 16 junior high schools in Yogyakarta who taught grades VII and VIII. Subjects were selected by stratified random sampling technique. Data collection techniques are carried out through questionnaires, observations, and interviews. Data were analyzed descriptively. The results of research on the readiness of junior high school mathematics teachers in the city of Yogyakarta to implement the 2013 curriculum in accordance with the criteria are quite good. Aspects of teacher insight about the 2013 Curriculum are quite good, the completeness of 2013 Curriculum documents is good, participation in curriculum education activities is not good, the ability to prepare lesson plans is quite good, the attitude of teachers towards the 2013 Curriculum is quite good, the completeness of facilities and infrastructure is quite good. 2013 curriculum. The results of the study are expected to be taken into consideration for policy making relating to the implementation of the 2013 Curriculum.